POLYMERS: THEIR APPLICATIONS IN DAILY LIFE AND ENVIRONMENTAL ISSUES - Hikmatova Hilola Ilkhom kizi; Nurmamatova Rukhshona Mardi kizi; Khudoyberdiyeva Farzona Ilkhom kizi; Rayimova Zarina Alisher kizi (Ta'lim innovatsiyasi va integratsiyasi, 2026)
Annotation: Polymers play a crucial role in modern life due to their versatile properties  and  wide-ranging  applications  across  industries.  From  packaging  and textiles  to  healthcare  and  electronics,  polymers  contribute  significantly  to  daily conveniences. However, their extensive use raises pressing environmental concerns, including pollution, waste management challenges, and ecological impacts. This article explores the dual nature of polymers—highlighting their benefits and the urgent need for sustainable solutions to mitigate environmental damage.